Authentic ELT Material Adaptation: Drawbacks, Prevalence and Solutions: The case of Wolkite University community school, Wolkite, Ethiopia. - Wondimtegegn, Fikremariam Yirgu (International Journal of Scientific Research and Management (IJSRM), 2020)
This paper examines the contributing issues that enhance students learning through adapting ELT materials and assessing its effectiveness forwarding to take measures. The study used both qualitative and quantitative approaches. The study was conducted a research by developing questionnaire, observation and document analysis. The data were collected from principals, teachers, students and woreda education officers. The data collected were arranged and organized for analysis and interpretation. Based on the analysed data, the study found out that limitations in the implementation of authentic material adaptation and how to use various adaptive techniques. Teachers lack of motive and interest to design and select language materials that fit the curriculum and closely correspond with the aims of the teaching program and the needs of the students. Thus, the study recommended that adapted materials should be carefully evaluated and selected before being used for a language classroom.